(untitled) (Latakia University Journal -Biological Sciences Series, 2018)
Soil water erosion is the most prominent environmental risk facing Syrian costal soils, especially from locations surrounding water basin. The severity of soil water erosion is greatly influenced by soil properties, slope, climate and vegetation and Rainfall intensity.To evaluate water erosion risk in Albasel Basin area using revised universal soil loss equation and geographic information system technology, this study wasconducted Factor R was calculated using un equation after collecting rain fall data during2007-2016. Factor K was calculated as well for every soil sample after estimating soil texture, structure, hydrolic conductivity and organic matter. Local distribution of K values was showed in a map, and slop factor was determined using DEM(Digital Elevation Model) ,slop degree was showed as well by a map using ArcGIS program . Land cover factor was calculated using NDVI and factor C was presented in a map by introducing NDVI map in equation using ArcGis program . To get the map of erosion risk , maps of LS , C ,k were multiplied with R values and the resulted was classified in 4 classes according to erosion risk (, low, medium, hard, and very hard). The study showed that R factor values 37, K factor values ranged between 0.09- 0.29, Ls values were between 0 - 44 , while factor C values were between 0.05-0.76 The study showed as well that regions which suffered from a very erosion risk form 16% of total area of studied region , it localized on river sides which feed lake basin and cover about 12.86 Km2 of area. يعد الانجراف المائي للتربة من ابرز المشاكل البيئية التي تتعرض لها ترب الساحل السوري وبشكل خاص الترب المحيطة بالأحواض المائية في محافظة طرطوس. وتتأثر شدة الانجراف بكل من خواص التربة, درجة الميل, الغطاء النباتي والشدة المطرية ..الخ. يهدف هذا البحث إلى تقييم خطر الانجراف المائي في منطقة حوض سد الشهيد باسل الأسد في طرطوس باستخدام تقانة نظم المعلومات الجغرافية (GIS) والمعادلة العالمية المعدّلة (RUSLE) . تم حساب العامل R من علاقة حسابية بعد جمع بيانات الهطول المطري للفترة الواقعة بين 2007-2016, من محطة الأرصاد في صافيتا ,العامل k تم حساب قيمته لكل عينة ترابية وذلك بعد تحديد كل من القوام , البناء الناقلية الهيدروليكية –المادة العضوية) , واعدت خارطة تبين التوزيع المكاني لقيم K.عامل درجة الميل تم تحديده باستخدام DEMلمنطقة الدراسة حيث تم إعداد خارطة لدرجة الميل أدخلت في علاقة رياضية من خلال برنامج ArcGIS للحصول على خارطة العامل LS,أما عامل الغطاء النباتيC فقد تم حسابه باستخدام NDVI لمنطقة الدراسة واعدت خارطة العامل C لاحقا بإدخال خارطة NDVI إلى علاقة حسابية باستخدام ArcGIS . للحصول على خارطة خطر الانجراف . تم حساب جداء خرائط كل من (LS,C,K,) مع قيمة R وتم تصنيف الخارطة الناتجة إلى أربع مراتب حسب خطورة الانجراف (منخفض –– متوسط –شديد –شديد جدا). أظهرت الدراسة إن قيمة العامل R تساوي 37 وقيم العامل K قد تراوحت بين 0.09 و0.29 أما قيم العامل LS فقد تراوحت بين 0و44 في حين تراوحت قيم العامل Cبين0.05 و0.76 كما أظهرت الدراسة إن المناطق التي تعاني من خطر انجراف شديد جدا تشكل (16%)من المساحة الكلية لمنطقة الدراسة وهي تقع في الجهة الشمالية من منطقة الدراسة وتغطي مساحة قدرها (12.86)كم2.